The study of the mother-child binomium: description and general results - Ruy Laurenti; Maria Helena Prado de Mello Jorge; Sabina Léa Davidson Gotlieb; Bruno Zoca de Oliveira; Elaine Cristina Pimentel (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2015)
OBJECTIVE: The present study investigated the characteristics of women during pregnancy/immediate postpartum cycles and the product of their pregnancy. METHOD: Data collection was conducted for a period of three months in 2011, in six maternity hospitals in the State of São Paulo. The data were obtained in an interview with the women after the end of the pregnancy and collected from hospital records. The sample included 7,058 women hospitalized for abortion or childbirth in five hospitals from SUS (Unified Health System) and from only one hospital for private health insurance patients and their 6,602 conceptuses (live births and stillborns). Statistical analysis was based on χ2 tests, with a significance level of α = 5%. RESULTS: It was observed that 6,530 women gave birth and 528 showed interruption of pregnancy. Regarding age, 1,448 were teenagers (20.5%). There were no deaths during hospitalization and 99.8% of women received a medical discharge. Maternal morbidity in the current pregnancy was analyzed, showing urinary tract infection, anemia and excessive vomiting as the main problems. The rate of cesarean sections accounted for 31.1% and complications in childbirth and postpartum were shown, respectively, by 834 (12.8%) and 265 (4.1%) women. The characteristics of the conceptuses were also studied: gestation length (9.3% of preterm among live births, and 68% among the stillborn); birth weight (underweight in 8.2% among live births, and 66% among the stillborn) and morbidity, measured by congenital anomalies and other diseases; these diseases were responsible for ICU stay, transfers to better-equipped hospitals (10 cases) and 37 deaths. Thirteen live births were still hospitalized at the end of the investigation.